Auditor Switching in the Economic Crisis: The Case in Greece - Maggina, Anastasia; Black, Ervin; Burton, Gre (International Journal of Accounting and Economics Studies, 2013)
This study examines auditor switching using discriminant analysis and logistic regression. These two statistical techniques have been employed to show both whether auditor switching can be forecasted and which method better fits the data for companies listed on the Athens Stock Exchange.  Using logistic analysis, auditor switching can be forecasted with prediction accuracy which exceeds 92.0 percent. In addition, we find that four financial ratios (Working Capital/Total Assets, Return on Assets, Market Value of Equity/Book Value of Total Debt, Sales/Total Assets) help explain the discrimination between companies that switch auditors and those that do not switch auditors.